Cancer phenomics research hotspots and development trends: a bibliometric analysis from 2000 to 2023 - Shupeng Chen; Jie Liu; Nana Tang; Yingjian Zeng (Discover Oncology)
Abstract The emerging field of cancer phenomics provides comprehensive insights into tumor heterogeneity, promoting advances in personalized oncology. This study explores current research hotspots and future development trends in cancer phenomics through a bibliometric analysis of research from 2000 to 2023. Using data from the Web of Science Core Collection, we analyzed 1260 publications to identify global contributions and collaborative networks. Employing CiteSpace and VOSviewer tools, we examined research trends, highlighting disease progression, multi-omics integration, and phenotypic drug discovery as major focus areas. Key findings reveal that the United States, China, and the United Kingdom are leading contributors, with top institutions such as Harvard Medical School advancing research and fostering international collaboration. Additionally, the analysis underscores the prominence of double-positive (DP) T cells and natural killer (NK) cells in cancer immunology, showcasing their potential roles in phenotypic screening and cancer therapeutics. Despite advancements, the study notes ongoing challenges in translating phenomics research to clinical applications, suggesting that enhanced global partnerships and technological integration are essential. This analysis offers valuable perspectives for future research and highlights phenomics' transformative potential in precision oncology, advocating for its role in advancing cancer diagnosis, treatment, and prevention.